DNA methyltransferase inhibitor 5'-azacytidine ameliorates autoimmune arthritis in mice - Tóth Dániel M.; Ocskó Tímea; Balog Attila; Markovics Adrienn; Mikecz Katalin; Kovács László; Jolly Meenakshi; Bukiej Aleksandra A.; Ruthberg Andrew D.; Vida András; Block Joel A.; Glant Tibor T.; et al. (2019)
Disease-associated, differentially hypermethylated regions have been reported in rheumatoid arthritis (RA) but no DNA methyltransferase inhibitors have been evaluated in either RA or in any animal models of RA. The present study was conducted to evaluate the therapeutic potential of 5'-azacytidine (AzaC), a DNA methyltransferase inhibitor, and explore the involved cellular and gene regulatory networks in the context of autoimmune arthritis.Disease-associated genome-wide DNA methylation profile was explored by MIRA-chip in arthritic B cells. Mice with proteoglycan-induced arthritis (PGIA) were treated with AzaC. AzaC effect on the pathogenesis of PGIA was explored by (i) measuring serum IgM and IgG1 antibody levels using ELISA, (ii) investigating efficiency of class-switch recombination and activation-induced cytidine deaminase (Aicda) gene expression using quantitative real-time PCR, (iii) monitoring germinal center (GC) formation by immunohistochemistry, and (iv) following B cell subpopulation alterations by flow cytometry. AzaC-induced regulation of Aicda gene was explored using RNA interference, chromatin immunoprecipitation and luciferase assays.We explored arthritis-associated hypermethylated regions in mouse B cells and demonstrated that DNA demethylation had a beneficial effect on autoimmune arthritis. AzaC-mediated demethylation of the epigenetically inactivated aryl hydrocarbon receptor (Ahr) gene resulted in suppressed expression of Aicda gene, reduced class-switch recombination and compromised GC formation. Ultimately, this process leaded to diminished IgG1 antibody production and ameliorated of autoimmune arthritis in mice.DNA hypermethylation plays a leading role in pathogenesis of autoimmune arthritis and its targeted inhibition has therapeutic potential in arthritis management. This article is protected by copyright. All rights reserved.